Association of a novel frameshift variant and a known deleterious variant in MMR genes with Lynch syndrome in Chinese families - Juyi Li; Haichun Ni; Xiufang Wang; Wenzhuo Cheng; Li Li; Yong Cheng; Chao Liu; Yuanyuan Li; Aiping Deng (World Journal of Surgical Oncology, 2024)
Abstract Background Lynch syndrome (LS) is the most common hereditary colorectal cancer (CRC) syndrome. This condition is characterized by germline variants in DNA mismatch repair (MMR) genes, including MLH1, MSH2, MSH6, and PMS2. In this study, we analyzed the molecular defects and clinical manifestations of two families affected with CRC and proposed appropriate individual preventive strategies for all carriers of the variant. Methods We recruited two families diagnosed with CRC and combined their family history and immunohistochemical results to analyze the variants of probands and those of other family members by using whole exome sequencing. Subsequently, gene variants in each family were screened by comparing them with the variants available in the public database. Sanger sequencing was performed to verify the variant sites. An online platform ( https://www.uniprot.org ) was used to analyze the functional domains of mutant proteins. Results A novel frameshift variant (NM_001281492, c.1129_1130del, p.R377fs) in MSH6 and a known deleterious variant (NM_000249.4:c.1731G > A, p.S577S) in MLH1 were identified in the two families with CRC. Using bioinformatics tools, we noted that the frameshift variant reduced the number of amino acids in the MSH6 protein from 1230 to 383, thereby leading to no MSH6 protein expression. The silent variant caused splicing defects and was strongly associated with LS. 5-Fluorouracil-based adjuvant chemotherapy is not recommended for patients with LS. Conclusions The novel frameshift variant (MSH6, c.1129_1130del, p.R377fs) is likely pathogenic to LS, and the variant (MLH1, c.1731G > A, p.S577S) has been further confirmed to be pathogenic to LS. Our findings underscore the significance of genetic testing for LS and recommend that genetic consultation and regular follow-ups be conducted to guide individualized treatment for cancer-afflicted families, especially those with a deficiency in MMR expression.